Characteristics of real-world gaseous exhaust emissions from cars in heterogeneous traffic conditions. (June 2021) - Kuppili, Sudheer Kumar; Dheeraj Alshetty, V.; Diya, M.; Shiva Nagendra, S.M.; Ramadurai, Gitakrishnan; Ramesh, A.; Gulia, Sunil; Namdeo, Anil; Maji, Kamal; Bell, Margaret; Goodman, Paul; Hayes, Enda; et al.
Highlights: CO, HC, and NO Emission factors for both diesel and petrol passenger cars are reported. Passenger cars, tested on five study routes in Delhi have different emission factors. Average emission factors of CO, HC, and NO were 3.8, 0.3, and 0.54 g/km, respectively. Emission rates vary as changes in speed and acceleration rates. Emission factors were lowest at 40–60 kmph speed range. Abstract: In this study, researchers have explored real-world driving conditions and developed emission factors for 58 passenger cars using on-board emission measurement technique while driving on five different routes in Delhi. The measured average emission factors of CO, HC, and NO were 3.99, 0.34, and 0.54 g/km for diesel vehicles, 7.26, 0.17, and 0.62 for petrol vehicles respectively. Road, traffic, vehicle type, and driving characteristics affect the quantity of emissions released. However, speed and acceleration significantly impact emission rates increasing with the increase in speed and acceleration. Also, emissions were minimal at 40–60 kmph and −0.5–0.5 m/s 2 . The estimated city-wide CO, HC, and NO emissions were 60.8, 4.8, and 9.72tonnes/day. These results demonstrate the importance of monitoring the real-world exhaust emissions given the substantial difference between test cycle measurements used for compliance testing of new vehicles.